2012
DOI: 10.1538/expanim.61.467
|View full text |Cite
|
Sign up to set email alerts
|

Data on Wistar Hannover Rats from a General Toxicity Study

Abstract: Abstract:The aim of this study was to collect data on chronological changes in clinical laboratory tests, pathological examinations, and hepatic drug-metabolizing enzymes from Wistar Hannover rats at 8, 10, 19, and 32 weeks of age. The serum triglyceride concentration and the serum LDL cholesterol level were higher in males than in females at all ages. In contrast, serum total protein and creatinine concentrations and cholinesterase activity were lower in males than in females. In addition, sex differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Increased relative organ weights of the testes, ovaries and thymus which were considered to be biologically sig-SD rats, absolute weights of heart, kidney and liver were lower in Wistar Han rats than those seen in SD rats and Histopathologic examination revealed increased incidence of corneal mineralization in Wistar Han rats, which is considered to be relevant to the corneal opacities observed during ophthalmology. These lesions were TM :WIST rats and Crl:WI(Han) rats (Hashimoto et al, 2011;Yamatoya et al, 2012). Other histopathologic changes in Wistar Han rats were comparable to those in SD rats and no remarkable changes were observed in macroscopic pathology in either strain of rat.…”
Section: Discussionmentioning
confidence: 90%
“…Increased relative organ weights of the testes, ovaries and thymus which were considered to be biologically sig-SD rats, absolute weights of heart, kidney and liver were lower in Wistar Han rats than those seen in SD rats and Histopathologic examination revealed increased incidence of corneal mineralization in Wistar Han rats, which is considered to be relevant to the corneal opacities observed during ophthalmology. These lesions were TM :WIST rats and Crl:WI(Han) rats (Hashimoto et al, 2011;Yamatoya et al, 2012). Other histopathologic changes in Wistar Han rats were comparable to those in SD rats and no remarkable changes were observed in macroscopic pathology in either strain of rat.…”
Section: Discussionmentioning
confidence: 90%
“…In recent years, Wistar Hannover (WH) rats have become increasingly commonly used for toxicological studies in Japan, and several studies on their suitability for this purpose have been published 6 , 7 , 8 . In our own studies to collect background data for a subchronic (26-week) general toxicity study, we found that the pattern of CL regression differed between WH and Sprague-Dawley (SD [Crl:CD]) (SD) rats.…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, RccHan TM :WIST (Wistar Hannover) rats were introduced to Japan as experimental animals for toxicity testing of pharmaceuticals. However, relatively little background data are available on Wistar Hannover rats (Okamura et al 2011; Yamatoya et al 2012). In a background data study gathered from a 26-week study and carcinogenicity study that used Wistar Hannover rats, we found spontaneous intranuclear and cytoplasmic inclusions in the proximal tubular epithelium.…”
Section: Introductionmentioning
confidence: 99%